Analysis of laminated Composite Structures - Alsubari, Saleh Mohammed; Chaffoui, H.; Nagi, .S (Journal of Amran University, 2024)
In this paper, we study the distribution of the constraints according to the thickness and analyze the mechanical behavior in inflection, while insisting on the interactions with the interfaces of the layers and the vicinities of the limiting edges. We detail these stages through the application by mentioning the characteristics of each model taken independently of the others. The results are presented in the form of a summary table and figures. To compare the various models of the theory of the plates, this characteristic of the edges enables us to consider the precision of the sinusoidal model compared to the traditional models of the plate theory. We are interested in one of the current problems of the multilayer laminated composites, which is the analysis of the distribution of the stress fields in the vicinities of the edges and in the interfaces of the layers, which play a crucial role in the mechanical resistance of the laminates.